GAMBARAN PENYAKIT PERIODONTAL PADA PASIEN DIABETES MELLITUS YANG BERKUNJUNG KE KLINIK GIGI RUMAH SAKIT UMUM DAERAH KARANGASEM TAHUN 2OI3 - Ni Nengah Suti; Ni Ketut Ratmini; I Nyoman Wirata (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
Diabetes mellitusis closely related to abnormalities in the periodontal tissues. Patient with Diabetes Mellitus (DM) that is uncontrolled with bad oral hygieneand glucose or sugar level sare high is a good medium for bacterial growth in the mouth so it will be found the presence of gingival lnflammation from gingivitis to periodontitis and acute marginal teeth shake.This study aims to describe the Periodontal Disease in Diabetes Mellitus Patients who visited the Dental Clinic General Hospital of Karangasem Regency in 2013